Compatible solutes from halophilicbacteria from saltpans of Goa, India - Noha Inam Ameen,; Savita Kerkar,; Rakhee D Sinai Khandeparkar,; Shaheen Ekram Jaafar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Hypersaline environments in Goa harbour diverse microorganisms capable of thriving in a salinity range of 0-300 psu (0-30%) and elevated temperatures (20 – 50˚C). Samples of solar salt collected from the salt pans ofCurca, Ribandar, and Agarwado, Goa, India. were used for isolating extremely halophilic bacteria with modified Zobell Marine Agar (ZMA) with 20% crude salt from the respective salt pans. Among the 22 isolated strains, six isolatesو could proliferate on ZMA with 25% salinity. The main aim of the present study was to explore the presence and the type of compatible solutes in hypersaline bacteria. Different methods were used to lyse the cells to extract the compatible solutes which were intracellular metabolites. Morphological and biochemical analysis, and 16S rRNA sequencing used for identification, revealed a similarity to Chromohalobactersalexigens. The isolated strain was further assessed for the presence of different compatible solutes using chemical methods and High-Performance Liquid Chromatography (HPLC). Chromohalobactersalexigens was found to have multiple compatible solutes like glutamic acid, glutamine and betaine hydrochloride which enabled this organism to survive in high salt concentrations irrespective of the location of the salt pan and the salinity.